Evaluation of gastroprotective and ulcer healing activities of yellow mombin juice from Spondias mombin L. - Samara A Brito; Isabela S Barbosa; Cynthia L F de Almeida; Jonathan W de Medeiros; Jacinto C Silva Neto; Larissa A Rolim; Teresinha G da Silva; Rafael M Ximenes; Irwin R A \ de Menezes; Germana F R Caldas; Almir G Wanderley (PLoS ONE, 2018)
Spondias mombin L. (yellow mombin) is a tree with a nutritional fruit that is commonly consumed in the North and Northeast of Brazil, as the juice of its pulp is rich in antioxidant compounds. This study aimed to investigate the gastroprotective and ulcer healing activities of yellow mombin juice (YMJ) in Wistar rats, and to elucidate the possible involved mechanisms. Phytochemical characterization of the lyophilized fruit juice was performed by high-performance liquid chromatography (HPLC). The gastroprotective activity of YMJ was investigated in ethanol (25, 50, and 100% YMJ) and indomethacin (100% YMJ) models of acute gastric ulcer in rats. Then, the effect of YMJ on mucus production and gastric secretions, and the involvement of non-protein sulfhydryl groups and prostaglandins in the gastroprotective process were examined. Moreover, the ulcer healing effect of YMJ was investigated in a model of acetic acid-induced chronic ulcer through histological and immunohistochemical analyses. HPLC results identified the presence of epicatechin (7.1 ± 1.6 μg/mL) and quercetin (17.3 ± 2.5 μg/mL) in YMJ. Ethanol-induced gastric lesions were inhibited by YMJ (25, 50, and 100%) by 42.42, 45.09, and 98.21% respectively, and indomethacin-induced lesions were inhibited by YMJ (100%) by 58.96%, compared to control group. Moreover, YMJ reduced gastric content and total acidy by 57.35 and 71.97%, respectively, compared to the control group. Treatment with YMJ also promoted healing of chronic ulcer, regeneration of the gastric mucosa, and restoration of mucus levels in glandular cells, as confirmed by histological analysis. It also increased cellular proliferation, as demonstrated by high reactivity to Ki-67 and bromodeoxyuridine. In conclusion, YMJ was found to possess gastroprotective and ulcer healing activities that are correlated to its antisecretory action. These results support the commercial exploration of YMJ as a functional food.